Birds Diversity In The Karang Jangkong Rice Field Area, Mataram City - Muhammad Zulhariadi; Fitri Farah Fauziah (PENBIOS: JURNAL PENDIDIKAN BIOLOGI DAN SAINS, 2023)
Birds are an important part of an ecosystem and are part of biodiversity whose sustainability must be maintained to avoid the threat of extinction. The purpose of this study was to determine the diversity and dynamics of bird populations along with environmental parameters in rice fields based on the seasonal dimension (time) and plant species around the city of Mataram and to determine the food webs that make up the rice field ecosystem occupied by birds. Bird observation using the roaming method. The results showed that the value of bird species diversity using the Shannon-Wiener formula in the Karang Jangkong rice field area was 1.27 (moderate diversity). Based on the observations, 7 species of birds were found consisting of 6 families, namely Pycnonotidae, Estrildidae, Cisticolidae, Apodidae, Passeridae, and Pycnonotidae. The conclusion of this study is that in general, the Karang Jangkong rice field area has sufficient environmental carrying capacity as a habitat for various species of birds in the rice field area.